Managing the Human Resources of Mission Health Institutions: a Case Study of St. Patrick’s Hospital, Offinso - Dakorah, Dr. Joseph Sogdia (2012)
A thesis submitted to the Board of Postgraduate Studies, Kwame Nkrumah University of Science and Technology, Kumasi, in partial fulfilment of the requirement for the award of Master of Science Degree in Health Services Planning and Management, 1999